특허정보를 활용한 국내 반려동물 산업의 기술 융합 동향에 관한 연구: 네트워크 분석과 텍스트 마이닝 기법을 활용하여 - 이동현(Donghyeon Lee); 강주영(Juyoung Kang); 이한솔(Hansol Lee) (스마트미디어저널, 2025)
Due to the increasing trend of treating pets as family members, the pet-related industry has experienced significant growth and is being recognized as a key future industry. However, research using patent big data on the domestic pet industry remains limited. This study conducted three analyses to explore trends and technological convergence in the pet industry. First, patent data was collected using search queries from Wipson, and the convergence of pet-related technologies was analyzed using the IPC (International Patent Classification) codes. Second, the periods from 2015 to 2019 and from 2020 to 2024 were compared, using 2020 as a reference point when pet adoption rates increased significantly. Convergence patterns were analyzed based on the centrality of the patent classification codes. Third, the content of patents from each period was examined to identify key topics in pet technology. The analysis revealed that before 2020, 70% of patents began with the classification code B23B, a proportion that dropped to 40% after 2020. While patents related to materials and pet products dominated before 2020, functional pet food patents emerged as significant after 2020. Finally, topic modeling was conducted on the invention titles, using LDA (Latent Dirichlet Allocation) and perplexity metrics. ChatGPT4o was employed to generate and refine topic names, and topics with high similarity were merged, resulting in a final list of topics. 반려동물의 가족화 현상으로 반려동물 관련 산업이 크게 성장하고 있으며 미래 핵심 산업으로 주목받고 있으나, 국내 반려동물 산업에 대한 특허 빅데이터를 활용한 연구는 아직 부족하다. 본 연구에서는 반려동물 산업의 기술 융합 양상을 파악하기 위한 세 가지 분석을 진행하였다. 첫 번째로, 윕스온(wipson)에서 검색식을 활용하여 특허 데이터를 수집한 후, IPC (International Patent Classification) 특허 분류 코드를 활용하여 반려동물 관련 기술의 융합 발전 양상을 분석하였다. 두 번째로 2020년을 기준으로 2015~2019년, 2020~2024년으로 기간을 나눈 후 분류 중심성 척도를 기준으로 특허 분류 코드를 대조하여 융합 발전 양상을 비교하였다. 세번째로 각 기간의 반려동물 특허의 내용을 분석하여 관련된 토픽들을 도출하였다. 분석 결과, 2020년 이전 5개년도의 경우 B23B로 시작하는 특허의 비율이 70%였으나 2020년 이후에는 40%로 감소하였다. 2020년 이전에는 소재 및 반려동물 용품 관련 특허 출원이 주를 이루었고, 2020년 이후에는 반려동물 기능성 식품 관련 특허가 상위에 등장하였다. 이후 발명의 명칭을 대상으로 토픽 모델링을 진행하였다. LDA 토픽 모델링 분석과 Perplexity를 활용하였으며, ChatGPT4o을 활용하여 토픽의 명칭에 대한 후보를 추출, 선정하였다. 최종적으로, 유사도가 높은 토픽들을 통합하여 최종 토픽 리스트를 도출하였다.